Drug Use Evaluation In Diabetic Patients at Out Patient Department Gorakhpur - Tripathi Poonam, Pandey Awanish, Pandey Rishabh, Goswamy Shambaditya & Srivatava Rashmi (Archives of Global Professionals, 2010)
Objectives: The aim of the present study was to assess drug utilization in diabetes patients as a quantitative type of prescription auditing to generate data with respect to their extent variability of drug usage in a heath care system of the area of Gorakhpur.Material and Methods: The data for the study was collected from the survey conducted in February 2009-April 2009 at various hospitals of Gorakhpur. Two hundred diabetic patients were interviewed as a pre designed questionnaire based on clinical details. All the diabetic patients who visited the OPD during the study period enrolled in the study.Results: The pattern of drug prescription in diabetes showed that sulfonylurea (65%) and biguanides (65%) were most frequently prescribed followed by thiazolidinediones (23%)and alpha glucosidase inhibitors (3%). Insulin was prescribed in 31 (15.5%) patients. Among Most common co-existing illness was found hypertension (31.97 %). Majority of drugs were prescribed in oral dosage form (84.5 %) followed by Parenteral (15.5 %).Conclusion: It is concluded that the present prescribing pattern of antidiabetic drugs Gorakhpur does not completely meet standard guidelines of diabetic treatment. Hence there is a need to encourage physicians of Gorakhpur to follow the guidelines while treating diabetes.